PENERAPAN ECOPRENEURSHIP UNTUK MENUMBUHKAN MINAT BERWIRAUSAHA MAHASISWA PENDIDIKAN IPA UNHASY - Noer Af’idah; Lina Arifah Fitriyah; Oktaffi Arinna Manasikana, (Prosiding Seminar Nasional Sains, Teknologi, Ekonomi, Pendidikan dan Keagamaan (SAINSTEKNOPAK), 2021)
The application of ecopreneurship to Science Education students is carried out as an effort to support the vision and mission of Hasyim Asy'ari University as The Real University of Pesantren and Entrepreneurship. This research was conducted with the aim of providing knowledge and experience to students about making environmental-based entrepreneurial products. This activity was carried out during the Covid-19 pandemic through online lectures in two stages, namely, firstly providing information and knowledge about the importance of preserving the environment, utilizing and processing waste into useful and high-value products. The second stage is the project task of making entrepreneurial products with waste as the main raw material. The results of the assignment can be used as entrepreneurial product innovations, so that students are more creative in producing entrepreneurial products while supporting one of the government's programs to create a healthy and zero waste environment. This research activity can foster entrepreneurial and student interest, which can be seen from the average score of 88 interest in entrepreneurship.